Numerical Study on Several Stabilized Finite Element Methods for the Steady Incompressible Flow Problem with Damping - Jilian Wu; Pengzhan Huang; Xinlong Feng (Journal of Applied Mathematics)
We discuss several stabilized finite element methods, which are penalty, regular, multiscale enrichment, and local Gauss integration method, for the steady incompressible flow problem with damping based on the lowest equal-order finite element space pair. Then we give the numerical comparisons between them in three numerical examples which show that the local Gauss integration method has good stability, efficiency, and accuracy properties and it is better than the others for the steady incompressible flow problem with damping on the whole. However, to our surprise, the regular method spends less CPU-time and has better accuracy properties by using Crout solver.